Surgical Anatomical Landmarks of the Thoracolumbar Vertebral Column on Magnetic Resonance Imaging in Dogs. (24th June 2015) - Yeamans, C. L.; Haley, A.; Gutierrez‐Quintana, R.; Penderis, J.
Summary: Magnetic resonance imaging (MRI) in veterinary medicine profoundly improved spinal cord disease investigation in canine patients. We aimed to further describe the anatomical landmarks of the thoracolumbar junction in sagittal MRI sequences. MRI studies from 90 dogs were reviewed retrospectively, representing a broad cross section of breeds and body weights. The ratio of the distance from the dorsal aspect of the vertebral canal to the dorsal aspect of the transverse process or rib articulation relative to the length of L2 vertebra was determined for T12, T13, L1 and L2 vertebrae. A statistically significant difference was noted with the transverse processes being more ventrally located than the cranial fovea costalis. The lumbar transverse processes and rib articulations dramatically varied in shape, being oval or round, respectively. The sagittal image at the level of the lateral margin of the articular facet joint proved to be the most consistent for review of these structures.